Rapid positioning method of power line inspection unmanned aerial vehicle assisted by BeiDou ground-based augmentation station - Wen Bo; Donglai Wang; Yan Zhao; Quanzheng Li; Qian Liu; Yuri Wang (Energy Reports, 2021)
BeiDou high-precision power line inspection can improve the efficiency and automation level of inspection operations, reduce labor intensity, and save inspection costs. However, although the satellite-based augmentation technology can solve the problem of large-scale positioning, it will introduce too many parameters into the positioning system through the method of parameter estimation. As a result, the behavior of the equation deteriorates, which makes it difficult to separate some parameters, and the convergence time of ambiguity parameters is too long. Under normal circumstances, the satellite-based augmentation standard positioning service needs at least about 30 min to converge to the centimeter level, and the ground-based augmentation system can provide an accurate model. This paper proposes a fast positioning method for satellite-based augmentation assisted by the BeiDou ground-based augmentation station. The receiver adopts the least square method, combined with the extended Kalman filter positioning, to achieve the improvement of the regional positioning effect of the satellite-based augmentation system. Positioning accuracy error does not exceed 1.6 meters. The error in the three directions of X, Y, and Z can be converged to the centimeter level in about 8 min. It can significantly improve the convergence time of satellite-based augmentation, and maintain continuous, stable and high-precision positioning of unmanned aerial vehicle in power line inspection.